State building and nationalism: the lesson of Pietro Grilli di Cortona - Giampiero Cama (Italian Political Science, 2017)
The related development of states and nationalism in Europe was one of Pietro Grilli’s several fields of research. Also in this area of interest he showed his peculiar style, especially a peculiar ability to combine theoretical and empirical analysis and a skilful use of the historical comparative method. Pietro addresses this issue mainly in a very interesting and seminal book, Stati, nazioni e nazionalismi in Europa, where we can find a remarkable and exhaustive longitudinal analysis of the birth and evolution of states and nations in our continent. In this work he shows, as usual for him, his skill to organize different and complex variables in clear and effective conceptual and theoretical frameworks. In my tribute to a dear friend and to a prestigious scholar I will try to illustrate some relevant implications of this specific contribution.